Efecto del compuesto bacteriano dimetilhexadecilamina en la microbiota endofítica de la leguminosa modelo Medicago truncatula - Real Sosa, Kassandra Michelle (Universidad Michoacana de San Nicolás de Hidalgo, 2018)
Soil is an environment inhabited by diverse microorganisms, including bacteria. In the soil also grow the plant roots that interact with the microorganisms, shaping a microecosystem named rhizosphere. Plants and rizobacteria have co-evolved interchanging biochemical signals, where some are able to colonize the internal tissues of the plants without causing any damage, forming what has been called endophytic microbiota. In the present work was tested the hypothesis that the volatile organic compound dimethylhexadecylamine (DMHDA), produced by the actinobacteria Arthrobacter agilis UMCV2, acts as a signal molecule that modulate the endophytic colonization of the model plant Medicago truncatula by rhizobacteria, coming from soils with different traits. The bacterial communities from bulk soil and rhizosphere, as well as the endophytic communities from M. truncatula plants were characterized. M. truncatula plants were grown in vitro in presence of soil microbiota and concentrations of DMHDA in the range of 1 to 16 μM, and profiles of the endophytic plant microbiota structure were performed quantifying the DNA from actinobacteria, firmicutes, α-, β- and γ-proteobacteria classes, as well as the strain UMCV2 by quantitative PCR. A high concentration of bacterial DNA was found in the plant compartments of root and shoots. In particular, it was found that the plant growth in culture medium in a concentration range from 1 to 4 μM of DMHDA produced an enrichment in the relative abundance of the firmicutes and actinobacteria divisions, and a decrease of α- and β- proteobacteria. The addition of DMHDA compound lead to a bearly enrichment of A. agilis UMCV2, showing that the role of DMHDA during endophytic colonization is not specific to A. agilis UMCV2.

El suelo es un ambiente habitado por diversos microorganismos, incluyendo bacterias. En el suelo también crecen las raíces de las plantas que interactúan con los microorganismos presentes formando un microecosistema denominado rizosfera. Las plantas y las rizobacterias han coevolucionado intercambiando señales bioquímicas, donde algunas son capaces de colonizar los tejidos internos de las plantas sin causarles daños conformando lo que se ha denominado la microbiota endofítica. En el presente trabajo se puso a prueba la hipótesis de que el compuesto orgánico volátil dimetilhexadecilamina (DMHDA) producido por la actinobacteria Arthrobacter agilis UMCV2 actúa como una molécula mediadora para la colonización endofítica de la planta modelo Medicago truncatula por bacterias provenientes de suelos con características diferentes. Principalmente, se caracterizó a las comunidades bacterianas de suelo y rizósfera, así como a las comunidades bacterianas endófitas de M. truncatula. Plantas de M. truncatula fueron crecidas in vitro en presencia de extractos de microbiota del suelo y de diferentes concentraciones de DMHDA en el intervalo de 1 a 16 μM, y se realizaron perfiles de la estructura de la microbiota endofítica de las plantas cuantificando el ADN de las divisiones actinobacteria y firmicutes y las clases α-proteobacteria, β-proteobacteria y γ-proteobacterias, así como de la actinobacteria A. agilis UMCV2 mediante PCR cuantitativo. Se encontró una elevada concentración de ADN bacteriano en los compartimientos vegetales de raíz y brotes. En particular, se encontró que el crecimiento de las plantas en medio de cultivo en un intervalo de concentraciones de 1 a 4 μM produjo un enriquecimiento en la abundancia relativa de las divisiones firmicutes y actinobacterias y un empobrecimiento de las clases α-proteobacteria y β-proteobacteria. La adición del compuesto DMHDA condujo a un enriquecimiento apenas perceptible de A. agilis UMCV2, mostrando que el efecto de la DMHDA en la colonización endofítica no es específico para esta especie.
Instituto de Investigaciones Químico Biológicas. Maestría en Ciencias en Biología Experimental
Keywords: info:eu-repo/classification/cti/6; IIQB-M-2018-1238; qPCR; Colonización endofítica; Microbiota; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/3968